Longitudinal Stroke Recovery Associated With Dysregulation of Complement System—A Proteomics Pathway Analysis - Nguyen, Vinh A.; Riddell, Nina; Crewther, Sheila G.; Faou, Pierre; Rajapaksha, Harinda; Howells, David W.; Hankey, Graeme J.; Wijeratne, Tissa; Ma, Henry; Davis, Stephen; Donnan, Geoffrey A.; Carey, Leeanne M. (Frontiers in Neurology, 2020)
Currently the longitudinal proteomic profile of post-ischemic stroke recovery is relatively unknown with few well accepted biomarkers or understanding of the biological systems that underpin recovery. We aimed to characterise plasma derived biological pathways associated with recovery during the first year post event using a discovery proteomics workflow coupled with a topological pathway systems biology approach. Blood samples (n = 180, ethylenediaminetetraacetic acid plasma) were collected from a subgroup of 60 first episode stroke survivors from the Australian START study at 3 timepoints: 3-7 days (T1), 3-months (T2) and 12-months (T3) post-stroke. Samples were analysed by liquid chromatography mass spectrometry using label-free quantification (data available at ProteomeXchange with identifier PXD015006). Differential expression analysis revealed that 29 proteins between T1 and T2, and 33 proteins between T1 and T3 were significantly different, with 18 proteins commonly differentially expressed across the two time periods. Pathway analysis was conducted using Gene Graph Enrichment Analysis on both the Kyoto Encyclopedia of Genes and Genomes and Reactome databases. Pathway analysis revealed that the significantly differentiated proteins between T1 and T2 were consistently found to belong to the complement pathway. Further correlational analyses were utilized to examine the changes in regulatory effects of proteins over time identified significant inhibitory regulation of clusterin on complement component 9. Longitudinal post-stroke blood proteomics profiles suggest that the alternative pathway of complement activation remains in a state of higher activation from 3-7 days to 3 months post-stroke, while simultaneously being regulated by clusterin and vitronectin. These findings also suggest that post-stroke induced sterile inflammation and immunosuppression could inhibit recovery within the 3-month window post-stroke.